Accountability and oversight in the Dutch intelligence and security domains in the digital age - Constantino, Jorge; Wagner, Ben (Frontiers in Political Science, 2024)
Accountability is considered a cornerstone of public administration and good governance. This study characterizes the relationship between the Dutch Intelligence and Secret Service (“AIVD”) and citizens (represented by parliament, courts, and oversight boards) as a complex actor-forum relationship. We utilize different accountability principles of public administration found in international and Dutch instruments and academic literature to propose workable principles of accountability for the AIVD. These proposed principles of accountability can be summarized as acting within duty, explainability, necessity, proportionality, reporting and record keeping, redress, and continuous independent oversight. Similarly, there are some conditions to support the workability of accountability principles. These conditions may be characterized as productive actor-forum relationships, cooperation, flexibility, value alignment, and learning and improving opportunities.